Dampak Kebijakan Proteksi terhadap Ekonomi Beras di Indonesia - Prajogo Utomo Hadi; Budi Wiryono (Jurnal Agro Ekonomi, 2005)
EnglishThe Indonesian rice economy has been increasingly squeezed since the agreements on agriculture under the WTO arrangements came into effect by 1 January 1995. This was attributed to excessive quantity of rice imports, especially since the economic crisis in mid 1997. The decreased world prices have severely affected the domestic prices that brought about the Indonesian rice to become increasingly less competitive. To deal with this crucial problem, the Indonesian government launched combined protection policies, including tariff and nontariff measures. Since 2000, the tariff rate is Rp 430/kg, and since 2003 the nontariff measure involves import arrangement, control and restriction. In relation to this problem, the objective of the present paper is to estimate the effects of the tariff and nontariff policies on the Indonesian rice economy both at the aggregate and farm levels. Using a partial equilibrium model, this research found that the protection policies have significantly reduced import quantity and, at the same time, significantly increased the domestic price, domestic production, producer’s surplus and farmer’s income. Elimination of one or both policies would bring back the Indonesian rice industry into bankruptcy. It is suggested, therefore, that: (1) The Indonesian government needs to retain the existing combined protection policies; (2) Indonesia together with other countries has to make more pressures on other (exporting) countries so as to reduce their export subsidies and domestic supports that would improve world prices; and (3) Always attempting improvement in domestic rice farming, processing and marketing so as to improve competitiveness. IndonesianKondisi perekonomian beras Indonesia makin terpuruk sejak diberlakukannya perjanjian pertanian WTO tanggal 1 Januari 1995. Hal ini disebabkan oleh membanjirnya impor, terutama sejak krisis ekonomi pada pertengahan 1997. Harga dunia yang terlalu rendah telah mengimbas ke pasar dalam negeri sehingga pertanian padi nasional makin tidak kompetitif. Menghadapi masalah ini, pemerintah Indonesia kemudian menempuh kebijakan proteksi, yang terdiri dari tarif dan nontarif. Sejak tahun 2000, tingkat tarif impor adalah Rp 430/kg, dan sejak tahun 2003 kebijakan nontarif mencakup pengaturan, pengawasan dan pembatasan impor. Sehubungan dengan itu, makalah ini bertujuan untuk mengestimasi dampak kebijakan tarif dan nontarif terhadap perekonomian beras nasional di tingkat makro agregat dan tingkat mikro usahatani. Dengan menggunakan pendekatan model keseimbangan parsial, dapat disimpulkan bahwa kebijakan proteksi telah berhasil secara signifikan menurunkan impor dan meningkatkan harga dalam negeri, jumlah produksi, surplus produsen dan pendapatan petani. Penghapusan salah satu kebijakan tersebut, apalagi keduanya, akan menyebabkan  pertanian padi nasional terpuruk kembali. Oleh karena itu disarankan agar : (1) Pemerintah perlu tetap mempertahankan kombinasi kebijakan proteksi yang ada; (2) Terus berjuang bersama dengan negara-negara lain untuk menekan negara-negara eksportir beras agar bersedia secara sungguh-sungguh menurunkan subsidi ekspor dan bantuan domestik sehingga harga dunia meningkat; dan (3) Terus mengupayakan perbaikan efisiensi usahatani padi, penggilingan dan pemasaran hasil di dalam negeri untuk meningkatkan daya saing.